Indoor microbial exposure increases complement component C3a and C-reactive protein concentrations in serum - Karhuvaara, Outi (Elsevier, 2025)
Indoor exposure to microbial growth, caused by moisture damage, has been an established health risk for several decades. It is likely that a damp indoor environment contains biological pollutants that trigger both the innate and adaptive branches of the immune system. In this study, we investigated the association between moisture damage related microbial exposure and serum C3a, C5a and CRP concentrations in Finnish adults. Serum C3a and CRP concentrations were elevated in individuals exposed to moisture damage and microbial growth in an indoor air environment. The elevated concentrations may be due to environmental factors present in moisture-damaged buildings. Complement activation and the resulting proinflammatory cleavage products may be a driving factor in inflammatory responses following exposure to indoor moisture damage and related microbial growth.